2008
DOI: 10.1209/0295-5075/84/40008
|View full text |Cite
|
Sign up to set email alerts
|

Trapping in complex networks

Abstract: We investigate the trapping problem in Erdos-Renyi (ER) and Scale-Free (SF) networks. We calculate the evolution of the particle density ρ(t) of random walkers in the presence of one or multiple traps with concentration c. We show using theory and simulations that in ER networks, while for short times ρ(t) ∝ exp(−Act), for longer times ρ(t) exhibits a more complex behavior, with explicit dependence on both the number of traps and the size of the network. In SF networks we reveal the significant impact of the t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
57
1
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 41 publications
6
57
1
8
Order By: Relevance
“…The impact of connectivity on transport properties has been put forward in [8,[23][24][25], where it was found in different examples that transport towards a target node can be favored by a high connectivity of the target, and different functional forms of the dependence of the MFPT on the target connectivity were proposed. On the other hand, the dependence of the MFPT on geometric properties, such as the volume of the network and the source to target distance, has been obtained recently in [26][27][28][29], where it was shown that the starting position of the random walker plays a crucial role in the target search problem.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of connectivity on transport properties has been put forward in [8,[23][24][25], where it was found in different examples that transport towards a target node can be favored by a high connectivity of the target, and different functional forms of the dependence of the MFPT on the target connectivity were proposed. On the other hand, the dependence of the MFPT on geometric properties, such as the volume of the network and the source to target distance, has been obtained recently in [26][27][28][29], where it was shown that the starting position of the random walker plays a crucial role in the target search problem.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the strong variability of the topology in the samples, the quenched properties could not coincide with the behavior found in the typical cases, as described by the probability distribution. Therefore, the study of quenched samples and deterministic topologies is a very interesting task [10,11,12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…A fundamental issue in network science is to understand diverse dynamical processes defined on different networks [4][5][6]. A paradigmatic dynamical process that has attracted increasing research interest is random walks [7][8][9][10][11][12][13][14][15][16][17], which have found a broad range of applications in various areas of science and engineering [18][19][20][21].…”
mentioning
confidence: 99%